Narrativas acerca da formação de professores de Educação Física em contexto de prática supervisionada - Cardoso, Inês; Batista, Paula; Graça, Amândio (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
This paper aims to capture the internal view of cooperating teacher about the reconstruction of the professional identity of three Physical Education preservice teachers. The selfdialogs reported in the logbook evidenced that the relationships require emotional balance between proximity and distance, making it easier to achievement of increased autonomy; and the reconstruction of the practical knowledge integrated the individual biographies, the knowledge construct in the initial teacher education, and the practice experiences.